Advances in biomaterials and regenerative medicine for primary ovarian insufficiency therapy - Sichen Zhang; Dashuai Zhu; Xuan Mei; Zhenhua Li; Junlang Li; Mengjie Xie; Halle Jiang Williams Lutz; Shaowei Wang; Ke Cheng (Bioactive Materials, 2021)
Primary ovarian insufficiency (POI) is an ovarian dysfunction that affects more than 1 % of women and is characterized by hormone imbalances that afflict women before the age of 40. The typical perimenopausal symptoms result from abnormal levels of sex hormones, especially estrogen. The most prevalent treatment is hormone replacement therapy (HRT), which can relieve symptoms and improve quality of life. However, HRT cannot restore ovarian functions, including secretion, ovulation, and fertility. Recently, as part of a developing field of regenerative medicine, stem cell therapy has been proposed for the treatment of POI. Thus, we recapitulate the literature focusing on the use of stem cells and biomaterials for POI treatment, and sum up the underlying mechanisms of action. A thorough understanding of the work already done can aid in the development of guidelines for future translational applications and clinical trials that aim to cure POI by using regenerative medicine and biomedical engineering strategies.